Avaliação da distribuição de elementos químicos em sedimento marinho, água do mar e material particulado atmosférico da Região Metropolitana da Grande Vitória - Dalfior, Bruna Miurim (2022)
The urban and industrial growth around the Greater Vitória Metropolitan Region has awakened the need to monitor the area in order to investigate the impacts on the environment. For this work purpose, the concentration of chemical elements in a sample of marine sediment and in a sample of atmospheric material from the Region of Grande Vitória do Espírito Santo and a sample of atmospheric material from the Region of Grande Vitória and apparent is determined. Marine sediment and seawater samples were collected at 23 sampling points (5 quarterly campaigns). As a sample of atmospheric particulate matter (PM) from 16 sampling points, they were provided by the State Institute for the Environment (IEMA). A decrease in the concentration of elements in the 2C and 5C campaigns was observed for the sediment samples, which may have occurred due to climatic conditions with large volume of precipitation and high energy events. Among the elements determined in the sediment samples, the concentrations of As, Cd, Zn, V and Mn stand out, since they were higher than recommended in the quality guides by calculating contamination indices, which may be related to a natural contribution from the Barreiras Group, as well as anthropic sources, such as mining. For seawater samples, higher concentrations of Pb, Mn, Zn and, above all, Fe were observed, with some samples showing values higher than those recommended for water intended for primary contact recreation. Similar behavior to that of the sediments was observed for the water samples from the 2C and 5C campaigns, which presented the lowest concentrations. Through the treatment of the concentration data of the sediment and water samples (dissolved fraction) using Pearson's correlation, it was possible to observe low correlations, however, mostly negative, suggesting a small transfer of the elements between the matrices. In order to better evaluate the distribution of elements in the sedimentary matrix and in the fraction dissolved in the water, the partition coefficient was calculated for all sampling points. Log Kd values greater than O were observed for most elements, indicating greater association with the sedimentary matrix, highlighting Mn and Fe; however, Ni and Zn behaved in opposite ways, indicating them with greater availabilty and appreciable presence in the dissolved fraction of water. For the study of atmospheric particulate matter, in addition to the elements previously determined in the sediments, rare earth elements (REEs) in PM samples and some possible sources of increment for this material were determined. The results found indicate that for each of the analyzed sources it would be possible to use a group of REEs to be used as chemical markers. It was also observed that the particulate material samples showed greater similarities with the sand and iron ore samples with and without suppressor resin than with the cement and asphalt samples. As concentrations for most of the elements studied in the particulate material matrix are not foreseen in the environmental quality guides, it was not possible to infer about the air quality of the Greater Vitória Region. In view of the results presented, the importance of monitoring this region is verified, considering the activities that take place in the surroundings of these environmental areas.